A case of Uterine didelphis with cervical atresia: A Case Report - Fantahun, Yitbarek; Kebede, Eskinder; Abate, Hamelmal (Ethiopian Journal of Reproductive Health, 2022)
Congenital uterine malformations are deviations from normal anatomy resulting due to defective fusion of Mullerian ducts or the paramesonephric ducts in the developing embryo. The prevalence of female genital tract anomalies is 4%-7% in general population and up to 8%-10% in women who have recurrent pregnancy loss.(1) The type and degree of anatomical distortion has associated health implications that may include, cyclical abdominal pain, reproductive failure, obstructed menses and inability to engage in sexual intercourse.(2) Uterus didelphys (double uterus) is a developmental abnormality that results from the failure of fusion of the Mullerian ducts leading to separate uterine cavities and 2 cervices 1. It is a rare anomaly accounting for 5% of all uterine anomalies. (3) Cervical agenesis is a rare Mullerian anomaly with an incidence of 1 in 80,000 females. (4) It represents 3% of all uterine anomalies. It is rarely associated with a functioning uterus (4.8%). Cervical agenesis is often associated with vaginal atresia (less than 50%). It is important to classify these anomalies for easy diagnosis and plan appropriate preoperative treatment.